2015
DOI: 10.1073/pnas.1510750112
|View full text |Cite
|
Sign up to set email alerts
|

SMARCAL1 maintains telomere integrity during DNA replication

Abstract: The SMARCAL1 (SWI/SNF related, matrix-associated, actin-dependent, regulator of chromatin, subfamily A-like 1) DNA translocase is one of several related enzymes, including ZRANB3 (zinc finger, RAN-binding domain containing 3) and HLTF (helicase-like transcription factor), that are recruited to stalled replication forks to promote repair and restart replication. These enzymes can perform similar biochemical reactions such as fork reversal; however, genetic studies indicate they must have unique cellular activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 46 publications
(104 reference statements)
1
74
0
Order By: Relevance
“…Yeast SWI/SNF is required for telomeric silencing (Dror and Winston 2004), and telomeric expansion (Tomar et al 2008). Mammalian cells lacking SMARCAL1, which is a SNF2 family ATPase but is not a subunit of the mammalian SWI/SNF complex, accumulate elevated levels of telomere-associated DNA damage (Poole et al 2015). Moreover, knockdown of the mammalian SWI/SNF enzyme subunit, ARID1A, reduces telomeric repeatcontaining RNA (TERRA) levels by at least twofold (Scheibe et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Yeast SWI/SNF is required for telomeric silencing (Dror and Winston 2004), and telomeric expansion (Tomar et al 2008). Mammalian cells lacking SMARCAL1, which is a SNF2 family ATPase but is not a subunit of the mammalian SWI/SNF complex, accumulate elevated levels of telomere-associated DNA damage (Poole et al 2015). Moreover, knockdown of the mammalian SWI/SNF enzyme subunit, ARID1A, reduces telomeric repeatcontaining RNA (TERRA) levels by at least twofold (Scheibe et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that SMARCAL1 depletion in 2 telomerase-positive cells lines, HeLa cells and MEFs, results in an increase in telomere damage. 25 Taken together, our data indicate SMAR-CAL1 function during telomere replication is a more universal requirement during telomere replication rather than an ALT-specific telomere repair pathway. …”
Section: Smarcal1 and Altmentioning
confidence: 61%
“…29 However, we were unable to detect any of these phenotypes in SMARCAL1-deficient cells. 25 This is the first case, to our knowledge, of persistent C-circles without the presence of other ALT phenotypes. Thus, Ccircles may not always indicate cells are using the ALT mechanism of telomere elongation.…”
Section: Smarcal1 and Altmentioning
confidence: 65%
See 2 more Smart Citations